ANALYSIS OF INVESTMENT PROGRAMS OF ENERGY COMPANIES - E. Kamchatova; A. Salmina (Вестник университета)
The aim of the study is to analyze the investment programs of energy companies. The subject of the research is the investment development program, which is a set of investment projects and activities aimed at improving the efficiency of production and economic activity of companies. The article presents the analysis of investment programs of development of the largest Russian energy companies, such as: PJSC RusHydro, state Corporation Rosatom, PJSC FGC UES, which are the leading players in the energy markets of electricity and power.